Scale, governance and the management of river basins: a case study from Central Iran - Molle, Francois; Mamanpoush, A.R. (Elsevier, 2012)
Aquatic socio-ecological systems show pervasive cross-scale interactions and problems of fit between ecosystems and institutions. Nested bio-hydrological processes within river basins are prone to thirdparty impacts, and equitable/sustainable management of water resources requires adequate governance patterns that both cover relevant scalar levels and handle cross-scale interactions. This paper provides the example of the Zayandeh Rud basin, in central Iran, and describes the historical evolution of water use at three different nested scales. It shows how the gradual overallocation of water resources (basin closure) and the manipulation of the hydrological cycle by the state and other actors have resulted in a constant spatial and social redistribution of water use and associated benefits and costs. State-centered modes of governance characterized by the priority to large-scale infrastructure, vested political and financial interests, lack of attention to local processes and hydrological interconnectedness, and the neglect of environmental degradation, must give way to forms of comanagement that better articulate the different levels of control and governance.